The Social Piety Index in Sumenep Regency by Analyzing Stability, Solidarity, and Mutual Cooperation - Al Humaidy, Muhammad Ali; Wahyuningrum, Sri Rizqi; Mubarak, Reza; Mariyam, Siti (Universitas Islam Negeri Madura, 2024)
The spirit of social care is an ethical demand, and religious values ​​must be practised. It implies that religious orientation involves the individual’s relationship with God (spiritual purity) and the way the individual interacts with other people (social piety). They range from criminal cases such as murder and rape to legal cases such as corruption and discrimination, to religious conflicts and terrorism. It indicates that religious communities are starting to lose their ethical dynamics. This research aims to describe the level of social piety of the people of Sumenep, focusing on the value of social stability, social solidarity, and cooperation. This research uses mixed methods. Data analysis involved 310 respondents in the productive age category (aged 15-64 years) spread across 27 sub-districts. Purposive sampling was used to determine the sample of respondents. Data collection was carried out through surveys using questionnaires, which also involved observation techniques and interviews as support. The results of the research show that the people of Sumenep obtained a perfect social piety index score (with a cumulative score of 83.36), including aspects of the social stability index of 84.71 (very good), the social solidarity index of 78.01 (good), and cooperation index 87.35 (very good). The achievement of the social piety index with a value of 83.36 in the very good category shows that the people of Sumenep have achieved a very good level of social harmonization.